Hecate: Lifting and Shifting On-Premises Workloads to an Untrusted Cloud - Ge, Xinyang; Kuo, Hsuan-Chi; Cui, Weidong (ACM Conference on Computer and Communications Security (CCS), 2022)
Despite the recent exponential growth in cloud adoption, businesses that handle sensitive data (e.g., health and financial sectors) are hesitant to migrate their on-premises IT infrastructure to the public cloud due to the lack of trust on the cloud provider. Confidential computing aims to move the cloud provider out of the trusted computing base. New hardware features such as AMD’s SEV-SNP can run a full virtual machine (VM) with confidentiality and integrity protection against the cloud. However, there exist challenges in supporting legacy operating systems and enforcing security policies (e.g., firewalls) in confidential VMs. In this paper, we present Hecate, an L1 hypervisor that runs inside a confidential VM enabled by SEV-SNP. Hecate can support legacy operating systems by running them in a nested VM and enforce various security policies on the nested VM based on the virtualization boundary. The key challenge in designing Hecate is that it cannot rely on the untrusted L0 hypervisor for nested virtualization. To solve it, we repurpose SEV-SNP’s newly added privilege dimension called Virtual Machine Privilege Levels (VMPLs) to enable virtualization for a single nested VM. We have built a prototype of Hecate based on the Linux KVM virtualization stack. Our prototype is capable of running MS-DOS, FreeBSD and vanilla Linux without any modification. It also supports security checks on the nested VM such as network firewalls and kernel integrity. When compared with a regular, non-confidential VM, the nested VM enabled by Hecate can achieve a throughput between 57% and 85% for real-world applications such as the Nginx web server and the MySQL database.